EVALUASI KINERJA GURU SDN 73/IX SIMPANG SUNGAI DUREN - Susanti, Try; Mursida, Mursida; Prihatini, Nurul; Dahlia, Dahlia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Teacher performance evaluation plays an important role in improving the quality of education through continuous professional development that supports enhanced competence and learning quality. This research was conducted using an in-depth literature study method on various scientific references related to teacher performance evaluation at SDN 73/IX Simpang Sungai Duren in Indonesia. The research stages included selecting relevant literature, collecting data through documentation, conducting qualitative analysis of 20 literature sources, and drawing conclusions based on four main research focuses. The results of the study indicate that the implementation of evaluation is still dominated by the top-down method, with the involvement of the principal and supervisor as the main evaluators, and minimal participation from students and parents. On the other hand, teacher competency achievements are classified as good in pedagogical and professional aspects, but are still weak in the application of learning technology and methodological innovation. The use of evaluation results is generally still administrative and has not been utilized strategically for career development or improving the quality of learning. Evaluation also faces various obstacles, such as time constraints, assessor subjectivity, and the absence of standardized standard instruments. Thus, a more participatory, fair, and sustainable teacher development-oriented evaluation approach is needed in order to support the transformation of quality education. ABSTRAK Evaluasi kinerja guru berperan penting dalam meningkatkan mutu pendidikan melalui pengembangan profesional berkelanjutan yang mendukung peningkatan kompetensi dan kualitas pembelajaran. Penelitian ini dilakukan dengan metode studi literatur yang mendalam terhadap berbagai referensi ilmiah terkait evaluasi kinerja guru SDN 73/IX Simpang Sungai Duren di Indonesia. Tahapan penelitian meliputi pemilihan literatur yang relevan, pengumpulan data melalui dokumentasi, analisis kualitatif terhadap 20 sumber pustaka, serta penarikan kesimpulan berdasarkan empat fokus utama penelitian. Hasil penelitian menunjukkan bahwa pelaksanaan evaluasi masih didominasi oleh metode top-down, dengan keterlibatan kepala sekolah dan pengawas sebagai evaluator utama, serta minimnya partisipasi dari siswa dan orang tua. Di sisi lain, capaian kompetensi guru tergolong baik dalam aspek pedagogik dan profesional, namun masih lemah dalam penerapan teknologi pembelajaran dan inovasi metodologis. Penggunaan hasil evaluasi umumnya masih bersifat administratif dan belum dimanfaatkan secara strategis untuk pengembangan karier atau peningkatan mutu pembelajaran. Evaluasi juga menghadapi berbagai kendala, seperti keterbatasan waktu, subjektivitas penilai, dan belum adanya instrumen baku yang terstandar. Dengan demikian, diperlukan pendekatan evaluasi yang lebih partisipatif, adil, dan berorientasi pada pembinaan guru secara berkelanjutan agar mampu mendukung transformasi pendidikan yang berkualitas.